BALANCING CASTE AND ECONOMIC RESERVATIONS: A CRITICAL ANALYSIS OF INDIA’S POLICY SHIFTS (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2026)
This study explores the evolution and impact of affirmative policy in India, particularly following the 103rd Amendment Act of 2019, which extended quota benefits to economically weaker sections (EWSs) of the upper castes. By delving into existing literature and analyzing census data from 1961 to 2011 alongside Annual Reports of the Department of Personnel & Training from 2013-14 to 2022-23, this research traces the historical development of reservation systems from pre Independence to post-Independence eras. It examines the socio-economic disparities faced by Scheduled Castes and Scheduled Tribes, the original beneficiaries of these policies. The study critically assesses the effectiveness of the 103rd Amendment in enhancing educational and employment opportunities for EWSs, juxtaposing this with the enduring caste-based inequalities. Findings indicate that while there have been significant improvements in literacy rates among SCs and STs, gaps persist when compared to the overall population. Additionally, the new amendment has not significantly improved public employment opportunities for non beneficiaries. The study underscores the need to realign reservation policies with their original objectives of addressing caste-based inequalities while also considering economic disparities to foster a more inclusive and equitable society.
Keywords: affirmative; discrimination; economically weaker; scheduled castes; scheduled tribes World Count: 4150